2021
DOI: 10.1186/s12877-021-02622-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations between homocysteine, inflammatory cytokines and sarcopenia in Chinese older adults with type 2 diabetes

Abstract: Background Sarcopenia, an age-related disease, has been implicated as both a cause and consequence of type 2 diabetes mellitus (T2DM) and a symbol of poor prognosis in older adults with T2DM. Therefore, early detection and effective treatment of sarcopenia are particularly important in older adults with T2DM. We aimed to investigate the prevalence of sarcopenia in Chinese older T2DM patients and explore whether homocysteine and inflammatory indexes could serve as biomarkers and participate in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
1
10
0
4
Order By: Relevance
“…that smoking and higher disease burden may increase serum homocysteine levels [32][33][34]. However, we were not able to observe a positive correlation between cigarette smoking and SA, which may be related to the fact that this study is only a single center study, and the selected patients may have selection bias.…”
Section: Discussionmentioning
confidence: 62%
“…that smoking and higher disease burden may increase serum homocysteine levels [32][33][34]. However, we were not able to observe a positive correlation between cigarette smoking and SA, which may be related to the fact that this study is only a single center study, and the selected patients may have selection bias.…”
Section: Discussionmentioning
confidence: 62%
“…This is supported by another study in 66 older adults that showed that vitamin B12 was 15% lower in the sarcopenic group compared to controls [ 40 ]. A more recent study [ 41 ] conducted in type 2 diabetes mellitus patients > 60 years also found a positive correlation between homocysteine and sarcopenia (defined by the updated criteria from the EWGSOP2 [ 42 ]) independent of HbA1c levels. From these studies, it is not clear if homocysteine is linked to specific components of sarcopenia (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…The association between higher BF % and sarcopenia could be explained by increased cytokines levels and insulin resistance. Cytokines secreted by adipose tissue such as interleukin-6, tumor necrosis factor-a may have catabolic effect on muscle (53). In addition, excess adiposity may reduce insulin action, which has pro-catabolic effects on muscle (8).…”
Section: Figurementioning
confidence: 99%